The tadpole of Phyllodytes praeceptor (Anura: Hylidae) - Santos, Leandro Oliveira; Costa, Renan Nunes; Solé, Mirco; Orrico, Victor Goyannes Dill (Zootaxa, 2019)
Phyllodytes Wagler 1830 is a genus composed of small species (SVL ranging 2.1–4.2 mm) that present odontoids and dwells in South America (Faivovich et al. 2005; Frost 2018). All known species of this genus are bromeligenous using bromeliads as shelter, calling site (males) and as egg deposition site (females). Offspring develops at the water retained in the axils (e.g., Bokermann 1966; Peixoto 1995; Haddad et al. 2013).